Utilization of Quizlet as an Interactive Quiz to Improve Student Learning Achievement - Rahim, Refka (World Psychology, 2023)
Along with the many advances in technology in the world of education, especially in website-based learning. Student learning achievement can be improved by using the Quizlet application. Quizlet is a platform used to make learning evaluations using the internet network. The purpose of this research is to determine the benefits of the Quizlet application as an interactive quiz to improve student learning achievement. This research uses quantitative methods using surveys and in-depth interviews, the survey was conducted online. The results of this research explain that the Quizlet platform can be used to create online-based interactive quizzes and can improve student achievement. The conclusion of this research explains that in using the applicationQuizlet really helps educators and students in the teaching and learning process, especially in implementing quizzes in learning. The limitation of this research is that the researcher only uses the Quizlet platform as an interactive quiz and the researcher hopes that future researchers can carry out the same research but with a more interesting Quiz application or can be used offline.